Clinical characteristics and sick leave associated with infectious mononucleosis in a real‐world setting in Germany. Issue 10 (6th August 2021) - Kap, Elisabeth J.; Konrad, Marcel; Kostev, Karel
Abstract: Background: Infectious mononucleosis (IM), mainly caused by the Epstein‐Barr virus, can result in prolonged symptoms. The objective of this study was to look at the length of sick leave, diagnosis of IM, treatment and comorbidities in a real‐world setting in Germany. Methods: This retrospective, cross‐sectional study used electronic medical record data from office‐based practices in Germany and included patients with an initial confirmed diagnosis of IM between the 1 January 1 2016 and December 31 2018. Patients of working age (18‐65 years) with statutory health insurance were included in order to look at the working population who would need a sick note for their employers in case of illness. Results: Epstein‐Barr virus was the most common cause of IM in this population of 1, 596 patients with an average age of 32 years. The majority of patients were women in all cohorts (~60%). Although CFS, myocarditis and thrombocytopenia were not recorded frequently around the index date, the occurrence did increase during the follow‐up period. Around half of patients received antibiotics. About 62% of all patients were on sick leave for an average of 20 calendar days around the time of their IM diagnosis. Only 1% were still on sick leave after 6 months. Conclusions: A small percentage of patients remained on continuous sick leave after 6 months, suggesting that the long‐term effect of IM on the ability to work was minor in our cohort. However, patients could still be experiencing symptoms that influence their quality of life.